2013
DOI: 10.1104/pp.112.211623
|View full text |Cite
|
Sign up to set email alerts
|

Role and Interrelationship of Gα Protein, Hydrogen Peroxide, and Nitric Oxide in Ultraviolet B-Induced Stomatal Closure in Arabidopsis Leaves    

Abstract: Heterotrimeric G proteins have been shown to transmit ultraviolet B (UV-B) signals in mammalian cells, but whether they also transmit UV-B signals in plant cells is not clear. In this paper, we report that 0.5 W m 22 UV-B induces stomatal closure in Arabidopsis (Arabidopsis thaliana) by eliciting a cascade of intracellular signaling events including Ga protein, hydrogen peroxide (H 2 O 2 ), and nitric oxide (NO). UV-B triggered a significant increase in H 2 O 2 or NO levels associated with stomatal closure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
78
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 72 publications
10
78
2
4
Order By: Relevance
“…Neither of these effects were readily reversed 24 h after the end of irradiation, consistent with our finding that stomatal closure is maintained by the high levels of NO remaining almost 24 h after UV-B exposure. It has been demonstrated that low levels of UV-B induce NO and ROS in some tissues and plant species (Zhang et al, 2003;An et al, 2005;He et al, 2005He et al, , 2013Qu et al, 2006). However, in our work, the low UV-B radiation used did not induce NO and H 2 O 2 production, explaining the lack of stomata closure.…”
Section: Uv-b For 3 H (+Uv-b) or Not In Controls (-Uv-b)contrasting
confidence: 54%
See 2 more Smart Citations
“…Neither of these effects were readily reversed 24 h after the end of irradiation, consistent with our finding that stomatal closure is maintained by the high levels of NO remaining almost 24 h after UV-B exposure. It has been demonstrated that low levels of UV-B induce NO and ROS in some tissues and plant species (Zhang et al, 2003;An et al, 2005;He et al, 2005He et al, , 2013Qu et al, 2006). However, in our work, the low UV-B radiation used did not induce NO and H 2 O 2 production, explaining the lack of stomata closure.…”
Section: Uv-b For 3 H (+Uv-b) or Not In Controls (-Uv-b)contrasting
confidence: 54%
“…Jansen and Noort (2000) found that UV-B may induce closure or opening in Vicia faba stomata, depending on the dose. Similarly, in Arabidopsis (Arabidopsis thaliana), very low fluence rates of UV-B stimulate stomatal opening (Eisinger et al, 2003), whereas a higher irradiance induces stomatal closure in the wild-type ecotype Wassilewskija (Ws; He et al, 2013). However, it is unknown whether UVR8 participates in the regulation of stomatal aperture by UV-B.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However the treatment of these plants with the donor of NO led to the ability of implication to close stomas. On the other hand, the treatment with hydrogen peroxide of mutants nia1-2, defective in nitric oxide synthesis, did not cause similar effect [6].…”
mentioning
confidence: 99%
“…The given effects were suppressed both by the catalase, and the scavenger of nitric oxide PTIO (2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide) [5]. There is a reason to suppose that the hydrogen peroxide plays the role of an inducer, causing the accumulation of NO, which is directly involved in the regulation of the state of stomas [6]. In Arabidopsis mutants atrbohD/F, defective in the activity of NADPH oxidase and not producing enough hydrogen peroxide, the closing of stomas, induced by the action of UF-B, did not take place.…”
mentioning
confidence: 99%